Answer:u= -4
Step-by-step explanation:
9+10 = 21 you stupid you stupid no I’m not
Answer:
152 ![\text{cm}^2](https://tex.z-dn.net/?f=%5Ctext%7Bcm%7D%5E2)
Step-by-step explanation:
We know that the total surface area of a cuboid is the sum of the surface area of all six of its faces.
We also know that each opposing side has the same surface area. Thus the total surface area is equal to:
(
)
M is the independent variable
Answer:
<h2>
10. C. (2, -1)</h2><h2>
11. B. (-2, -4)</h2>
Step-by-step explanation:
10.
![\left \{ {{x-2y=4} \atop {4x+2y+6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-2y%3D4%7D%20%5Catop%20%7B4x%2B2y%2B6%7D%7D%20%5Cright.)
The y values cancel out if you add the equations
5x = 10
x = 2
plug in x
2 - 2y = 4
-2y = 2
y=-1
Answer: C. (2, -1)
11.
![\left \{ {{6x-2y=-4} \atop {-4x+3y=-4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B6x-2y%3D-4%7D%20%5Catop%20%7B-4x%2B3y%3D-4%7D%7D%20%5Cright.)
In order to get terms to cancel out, multiply the top by 3 and bottom by 2
![\left \{ {{18x-6y=-12} \atop {-8x+6y=-8}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B18x-6y%3D-12%7D%20%5Catop%20%7B-8x%2B6y%3D-8%7D%7D%20%5Cright.)
The y values cancel out if you add the equations
10x = -20
x = -2
plug in x
6(-2) - 2y = -4
-12 - 2y = -4
-2y = 8
y = -4
Answer: B. (-2, -4)